Effect of the photoinitiator system on the polymerization of secondary methacrylamides of systematically varied structure for dental adhesive applications. Issue 3 (March 2020) - Barcelos, L.M.; Borges, M.G.; Soares, C.J.; Menezes, M.S.; Huynh, V.; Logan, M.G.; Fugolin, A.P.P.; Pfeifer, C.S.
Abstract: Objective: The aim of this study was to investigate the influence of the photoinitiator system on the polymerization kinetics of methacrylamide-based monomers as alternatives to methacrylates in adhesives dental-based materials. Methods: In total, 16 groups were tested. Monofunctional monomers (2-hydroxyethyl methacrylate) – HEMA; (2-hydroxy-1-ethyl methacrylate) −2EMATE, (2-hydroxyethyl methacrylamide) – HEMAM; and ( N -(1-hydroxybutan-2-yl) methacrylamide) −2EM; were combined with bifunctional monomers containing the same polymerizing moieties as the monofunctional counterparts (HEMA-BDI; 2EMATE-BDI; HEMAM-BDI; and 2EM-BDI) at 50/50 M ratios. BHT was used as inhibitor (0.1 wt%) and the photoinitiators used were: CQ + EDMAB (0.2/0.8), BAPO (0.2), IVOCERIN (0.2), and DMPA (0.2), in wt%. The polymerization kinetics were monitored using Near-IR spectroscopy (∼6165 cm −1 ) in real-time while the specimens were photoactivated with a mercury arc lamp (Acticure 2; 320−500 nm, 300 mW/cm 2 ) for 5 min, and maximum rate of polymerization (Rpmax, in %.sˉ̄ 1 ), degree of conversion at Rpmax (DC@Rpmax, in %), and the final degree of conversion (Final DC, in %) were calculated (n = 3). Initial viscosity was measured with an oscillating rheometer (n = 3). Data were analyzed using Two-way ANOVA for the polymerization kinetics and one–way ANOVA for the viscosity. Multiple comparisons were made using the Tukey's test (∝ = 0.05). Results: There was statistically significant interaction between monomer and photoinitiator (p < 0.001). For the methacrylates groups, the highest Rpmax was observed for HEMA + DMPA and 2EMATE + BAPO. For methacrylamides groups, the highest Rpmax were observed for HEMAM and 2EM, both with DMPA. Final DC was higher for the methacrylate groups, in comparison with methacrylamide groups, independent of the photoinitiators. However, for the methacrylamide groups, the association with BAPO led to the lowest values of DC. In terms of DC@Rpmax, methacrylate-based systems showed significantly higher values than methacrylamide formulations. DMPA and Ivocerin led to higher values than CQ/EDMAB and BAPO in methacrylamide-based compounds. BAPO systems showed de lowest values for both HEMA and HEMAM formulations. For the viscosity (Pa.s), only 2EM had higher values (1.60 ± 0.15) in comparison with all monomers. In conclusion, polymerization kinetics was affected by the photoinitiators for both monomers. Viscosity was significantly increased with the use of secondary methacrylamide. Significance: this work demonstrated the feasibility of using newly-synthesized methacrylamide monomers in conjunction with a series of initiator systems already used in commercial materials.